Prática social lazer de um grupo de mulheres do Jardim Panorama - Rio Claro – SP : processos educativos decorrentes - Cunha Júnior, Silvino Marques da (2016)
This study was developed in Multisport Jardim Panorama Gym, outlying district of the city of Rio Claro, in the state of São Paulo, with a group of twelve women who meet weekly for exercise, hiking, play and chat in leisure enjoyment context. The research had as main objective to characterize and educational processes triggered this group of women. It justified this study because leisure is a theme present in our society, but linked to financial and economic factors, leaving your background essence. The methodological approach used was qualitative research based on phenomenology. Therefore, we were held thirteen meetings on site, from the second half of 2015. From these meetings were held in notes field diaries, following performed data analysis procedure inspired by phenomenology, through the phenomenological reduction and construction of nomothetic matrix, in which the following categories were constructed: a) quality of life valuation, which was evident from the living, care and attention of one towards the other, the appreciation of the quality of life; B) Engagement and struggle, in which the engagement of the group was perceived by the commitment to a combined and charges for other and through this engagement strive for personal improvement, the group and the community in which they operate; C) Understandings about leisure, they present the understanding of the group of women about their leisure and experiences about leisure possibilities in the city. From the study, we can consider that triggered educational processes were learning and care of one towards the other, the maturing of political consciousness, the different forms of leisure enjoyment, affection and sensitivity, collective work, respect and solidarity with the other, as well as the researcher's learning with this group of women with joy and humor, even in bad weather, radiated attention, care and loveliness, favoring our humanization, our Being More.